Development of improved dual-diazonium reagents for faster crosslinking of tobacco mosaic virus to form hydrogels. Issue 50 (17th September 2019) - Ma, Dejun; Chen, Zhuoyue; Yi, Long; Xi, Zhen
Abstract : Improved dual-diazonium reagents were developed for more efficient crosslinking of tobacco mosaic virus to form hydrogels. Abstract : New bench-stable reagents with two diazonium sites were designed and synthesized for protein crosslinking. Because of the faster diazonium-tyrosine coupling reaction, hydrogels from the crosslinking of tobacco mosaic virus and the reagentDDA-3 could be prepared within 1 min at room temperature. Furthermore, hydrogels with the introduction of disulfide bonds via DDA-4 could be chemically degraded by dithiothreitol. Our results provided a facile approach for the direct construction of virus-based hydrogels.